Effect of electrical stimulation as an adjunct to botulinum toxin type A in the treatment of adult spasticity: a systematic review. Issue 21 (9th October 2017) - Intiso, Domenico; Santamato, Andrea; Di Rienzo, Filomena
Abstract: Objective: To investigate whether electrical stimulation (ES) as an adjunct to BTX-A boosts botulinum activity and whether the combined therapeutic procedure is more effective than BTX-A alone in reducing spasticity in adult subjects. Data sources: A search was conducted in PubMed, EMBASE, Cochrane Central Register, and CINAHL from January 1966 to January 2016. Study selection: Only randomized controlled studies (RCT) involving the combination of BTX-A and ES were considered. RCTs were excluded if BTX plus ES was investigated in animals or healthy subjects; certain techniques were used as an adjunct to BTX-A, but ES was not used; BTX-A or ES were compared but were not used in combination. ES was divided into neuromuscular stimulation (NMS), functional electrical stimulation (FES), and transcutaneous electrical nerve stimulation (TENS). Two authors independently screened all search results and reviewed study characteristics using the Physiotherapy Evidence Database (PEDro) scale. Results: Fifteen RCTs were pinpointed and nine studies were included. Trials varied in methodological quality, size, and outcome measures used. ES was used in the form of NMS and FES in seven and two studies, respectively. No study investigating BTX-A plus TENS was found. BTX-A plus ES produced significant reduction in spasticity on the Ashworth Scale (AS) and on the modified AS in seven studies, but only four showed high quality on the PEDro scale. Significant reduction in compound muscular action potential (CMAP) amplitude was detected after BTX-A plus ES in two studies. Conclusions: ES as an adjunctive therapy to BTX-A may boost BTX-A action in reducing adult spasticity, but ES variability makes it difficult to recommend the combined therapy in clinical practice. Implications for rehabilitation: Electrical stimulation (ES) as adjunct to botulinum toxin type A (BTX-A) injections may boost neurotoxin action in treating adult spasticity. Given the variability of ES characteristics and the paucity of high-quality trials, it is difficult to support definitively the use of BTX-A plus ES to potentiate BTX-A effect in clinical practice. A vast array of rehabilitation interventions combined with BTX-A have been provided in reducing spasticity, but the present evidence is not sufficient to recommend any combined therapeutic strategy.